Back to Basics: Environmental Cleaning. (25th June 2014) - Spruce, Lisa; Wood, Amber
Abstract: The need for a clean perioperative environment is a basic principle for all perioperative team members. Recent evidence suggests that the environment plays a role in the occurrence of health care–associated infections (HAIs), including surgical site infections. Frequently cleaning high‐touch surfaces helps prevent the spread of infections, and routinely cleaning and disinfecting the patient's environment can reduce the level and frequency of contamination and the risk of HAIs. Perioperative personnel should use a bundled approach to perform a standardized cleaning routine and implement a successful monitoring program.